2024
DOI: 10.1186/s12909-024-05090-1
|View full text |Cite
|
Sign up to set email alerts
|

Using simulation to introduce students and healthcare professionals to losses experienced by older adults: a pre-post analysis

Donna Prete,
Linda Tamburri,
Nicole Rolston
et al.

Abstract: Background To introduce students and healthcare professionals to losses experienced by older adults and instill compassion among interprofessional learners, an interactive narrative simulation activity was developed and incorporated in clinical staff orientation and student professional course work. Narrative simulation allows learners to incorporate skills of examination, exploration, sharing, and reflection applied to simulated losses and lived experience of the older adult to promote empathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The AIED event allowed undergraduate nursing students to experience a realistic encounter with an older adult, raising students’ awareness of their attitudes toward the geriatric population. This study’s results are like those of other studies that used simulation as an educational intervention to positively influence nursing students’ attitudes toward caring for older adults [ 11 , 12 ]. This study underscores the efficacy of the AIED event in challenging negative attitudes and promoting more positive perceptions of older adults among future nursing workforces.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The AIED event allowed undergraduate nursing students to experience a realistic encounter with an older adult, raising students’ awareness of their attitudes toward the geriatric population. This study’s results are like those of other studies that used simulation as an educational intervention to positively influence nursing students’ attitudes toward caring for older adults [ 11 , 12 ]. This study underscores the efficacy of the AIED event in challenging negative attitudes and promoting more positive perceptions of older adults among future nursing workforces.…”
Section: Discussionsupporting
confidence: 81%
“…Several authors have used geriatric simulation exercises and reflective discussions to expose healthcare professions to older adults. The intervention significantly improved empathy toward aging and increased confidence in providing geriatric care [ 11 , 12 ]. An integrative review by Magan et al found that past experiences with older adults and gerontology-focused teaching strategies effectively diminished ageist stereotypes and fostered positive attitudes and perceptions of older adults [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation